Effect of pH and Temperature on the degradation of ciprofloxacin and ofloxacin in aqueous solution. (Comprehensive Journal of Science, 2025)
This study aims to evaluate the impact of physical and chemical factors specifically pH andtemperature—on the stability and degradation of two fluoroquinolone antibiotics: Ofloxacin andCiprofloxacin in aqueous solutions. Standard solutions of varying concentrations were prepared,and their absorbance and maximum wavelength (λ max) were measured using a UV-Visspectrophotometer under different pH and temperature conditions.The results showed that an acidicmedium (pH = 4) increased the absorbance of both antibiotics, with slight changes in λ max.Elevated temperatures led to a decrease in absorbance, indicating gradual thermal degradation ofthe compounds.The study highlights the importance of understanding environmental influences onantibiotic efficacy and recommends further research involving additional factors and longerexposure periods to enhance pharmaceutical stability assessments.
Keywords: Ofloxacin ,Ciprofloxacin, Fluoroquinolones, UV-Vis Spectrophotometer , pH Effect ,Absorbance, λ max (Maximum Wavelength)